The Influence Of Managerial Ownership, Independent Commissioners, Audit Committee, Non-Performing Loans (Npl) And Loan To Deposit Ratio (Ldr) On Bank Financial Performance - Muhamad Muslih; Divna Putri Kusuma (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Company performance in the financial sector is a capability of a business institution to manage and supervise resources where the decrease and increase is given the impact of various indicators, for example financial risk and office management. This research is gonna explain managerial ownership, audit committees, independent commissioners, NPL or Non-Performing Loans and the Leon to Deposit Ratio or LDR which have an impact on increasing and decreasing ROA performance. The data collection here is data from the IDX or the Indonesia Stock Exchange regarding Subsector companies in 2017-2021 and the technique is purposive random sampling.  The results of the data are 15 sample companies in the banking subsector.  The results of this study are managerial ownership, independent commissioners, audit committees, Non-Performing Loom (NPL) and Loan to Deposit Ratio (LDR) simultaneously affect the bank's financial performance.  Partially, the impact that is limited to the audit committee only on the bank's financial performance while independent commissioners and managerial ownership, NPL and LDR have no impact on the bank's financial performance.